Persepsi Gen-Z Terhadap Stigma Musik Klasik Sebagai Selera Kalangan Atas Di Era Digital: Studi Anggota Paduan Suara Mahasiswa Universitas Gadjah Mada (PSM UGM) - Sinurat, Tobias Toga Prokhorus Nikanor (Jurnal Studi Pemuda, 2023)
This article explores the perception of Generation Z students towards classical music in the digital era. The era in which various streaming platforms have made accessing a wide range of music genres easier. Despite the easier access, classical music is still identified as a highbrow taste. Bourdieu’s theory of habitus and cultural capital has been challenged by Peterson’s theory of cultural omnivorousness, which suggests that individuals now tend to have more diverse and eclectic tastes, enjoying a range of cultural genres from both highbrow and lowbrow across the traditional hierarchical social class boundaries. However, this research indicates that Bourdieu’s theory on the cultural capital and upper-class habitus as elements shaping the taste for classical music remains highly relevant. By employing a phenomenological approach, the research focuses on the subjective experiences of UGM Student Choir members to understand their views on classical music as a taste of the upper class. This research finds that despite the growing access to digital music streaming, the perception of classical music as the taste of the highbrow class persists, especially because enjoying, appreciating, and understanding classical music still requires the knowledge attached to the habitus of the highbrow class.